Multi-Valued Neutrosophic Set for Quality Evaluation of Public Landscape Space Design Surrounding Historic and Cultural Districts Based on Computer-Aided Design - Yue Liu (Neutrosophic Sets and Systems)
The integration of Computer-Aided Design (CAD) into the evaluation of public landscape spaces surrounding historic and cultural districts presents a transformative approach to urban heritage planning. This study explores an uncertainty framework for assessing the quality of landscape designs through digital simulation, focusing on historical compatibility, aesthetic coherence, sustainability, accessibility, and community engagement. By leveraging CAD tools, planners and designers can visualize proposed interventions with high precision, enabling the assessment of both tangible and intangible heritage values. The methodology ensures that public spaces not only preserve the cultural identity of their surroundings but also enhance their usability and environmental performance. The proposed evaluation model contributes to evidence-based planning by bridging traditional conservation principles with contemporary digital technologies. This study uses Multi-Valued Neutrosophic Set (MVNS) to overcome uncertainty and vague information. This study uses eight criteria and seven alternatives to be evaluated.